2015
DOI: 10.4168/aair.2015.7.2.167
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Antibiotic Exposure, Bronchiolitis, and TLR4 (rs1927911) Polymorphisms in Childhood Asthma

Abstract: PurposeThe complex interplay between environmental and genetic factors plays an important role in the development of asthma. Several studies have yielded conflicting results regarding the 2 asthma-related risk factors: antibiotic usage during infancy and/or a history of bronchiolitis during early life and the development of asthma. In addition to these risk factors, we also explored the effects of Toll-like receptor 4 (TLR4) polymorphism on the development of childhood asthma.MethodsThis cross-sectional study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
0
11
0
1
Order By: Relevance
“…Previous studies have reported that the disease associations of TLR4 with chronic inflammatory disease include atherosclerosis, asthma, and rheumatoid arthritis [ 21 ]. It has been discovered that there is an association of TLR4 rs1927911 SNP with childhood asthma [ 22 ] and disease activity of rheumatoid arthritis [ 23 ] and type 2 diabetes mellitus [ 24 ]. Nicola et al reported that all components of the LPS receptor complex are expressed on thyrocyte, and they also detected that thyroid cells recognize and respond to LPS using Fisher rat thyroid cell line-5 cells [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the disease associations of TLR4 with chronic inflammatory disease include atherosclerosis, asthma, and rheumatoid arthritis [ 21 ]. It has been discovered that there is an association of TLR4 rs1927911 SNP with childhood asthma [ 22 ] and disease activity of rheumatoid arthritis [ 23 ] and type 2 diabetes mellitus [ 24 ]. Nicola et al reported that all components of the LPS receptor complex are expressed on thyrocyte, and they also detected that thyroid cells recognize and respond to LPS using Fisher rat thyroid cell line-5 cells [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in TLR family genes have been investigated using single nucleotide polymorphism (SNP) analysis and meta‐genome‐wide association studies (GWAS). Indeed, SNPs in the TLR4 gene are a risk factor for asthma, indicating that genetic variations of TLR family genes are related to susceptibility to allergic diseases.…”
Section: Toll‐like Receptorsmentioning
confidence: 99%
“…The SNPs enrolled in our data were selected based on previous published studies (Tal et al, 2004;Löfgren et al, 2010;Goutaki et al, 2014;Murawski et al, 2009;Mailaparambil et al, 2008;Amanatidou et al, 2008;Kresfelder et al, 2011;Janssen et al, 2007;Arruvito et al, 2015;Puthothu et al, 2006;Lee et al, 2015;Fan et al, 2003;Ricciardolo et al, 2004). All SNPs studied are bi-allelic.…”
Section: Polymorphism Screeningmentioning
confidence: 99%
“…The present study found that death from bronchiolitis is associated with SNP rs4986790 (TLR4), but no association was detected between bronchiolitis severity and SNP rs1927911 (TLR4). SNP rs1927911 (TLR4) was recently associated with an increased risk of asthma development in children with a history of bronchiolitis (Lee et al, 2015), so we are following up our patients to verify any association between bronchiolitis severity, the virus type, genetic polymorphisms, and asthma development. Environmental factors have also been shown to interact with the TLR4 genotype to modulate the RSV infection severity (Caballero et al, 2015).…”
Section: Toll Like Receptor 4 -Tlr4mentioning
confidence: 99%